2015
DOI: 10.1016/j.ress.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of industrial facilities to attacks with improvised explosive devices aimed at triggering domino scenarios

Abstract: Process- and chemical plants may constitute a critical target for a terrorist attack. In the present study, the analysis of industrial accidents induced by intentional acts of interference is carried out focusing on accident chains triggered by attacks with home-made (improvised) explosives. The effects of blast waves caused by improvised explosive devices are compared with those expected from a net equivalent charge of TNT by using a specific methodology for the assessment of stand-off distances. It is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…TATP is a very volatile and unstable explosive and is easily detonated accidently. Landucci et al (2015) estimates that TATP has an NEQ of 0.5–0.6 if manufactured in a controlled laboratory environment. Hargather and Settles (2007) found from experimental testing that the NEQ for TATP is 0.1–0.45, and is a function of distance from the charge.…”
Section: Illustrative Example: Person-borne Improvised Explosive Devimentioning
confidence: 99%
See 1 more Smart Citation
“…TATP is a very volatile and unstable explosive and is easily detonated accidently. Landucci et al (2015) estimates that TATP has an NEQ of 0.5–0.6 if manufactured in a controlled laboratory environment. Hargather and Settles (2007) found from experimental testing that the NEQ for TATP is 0.1–0.45, and is a function of distance from the charge.…”
Section: Illustrative Example: Person-borne Improvised Explosive Devimentioning
confidence: 99%
“…If TATP is stabilised with carbonaceous liquids and waxes its NEQ is even lower. The NEQ of TATP is also highly dependent on the quality of the final product, and is very sensitive to the temperature during its synthesis (Landucci et al, 2015). Even when made under ideal conditions the NEQ of TATP is highly variable.…”
Section: Illustrative Example: Person-borne Improvised Explosive Devimentioning
confidence: 99%
“…It can be applied as an oxygen component in the explosive composition. Landucci et al indicated that ammonium nitrate fuel oil (ANFO), based on the fertilizer grade of AN (AN-F), was less efficient and was characterized by a lower void fraction in comparison to the ammonium nitrate porous prill (AN-PP) counterpart [3]. Moreover, due to the European regulation [4], AN-F requires modification to be introduced to the market.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the European regulation [4], AN-F requires modification to be introduced to the market. However, despite this fact, it is this type of AN [3] that is usually used as the oxygen component in home-made explosives.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent concerns about weapons of mass destruction (WMD), explosions are by far the most common cause of mass-casualty incidents associated with terrorism [4]. A successful attack aimed at direct or indirect damage of target equipment by bombs or fire arms can trigger domino scenarios [5] and cause damages to multiple process units or eventually several neighbouring industrial site [6,7]. The terrorist attacks to Iraq's oil terminal in 2004 and largest refinery in 2015 are examples of terrorist attacks by improvised explosive devices (IEDs) to chemical plants [8,9].…”
Section: Introductionmentioning
confidence: 99%